(untitled) (Applied Biological Research, 2023)
Peanut and rice are the widely consumed food material all over the globe. The contamination of these commodities with aflatoxin is a big challenge and a major health concern. In present study, two aflatoxin producing fungi were the isolated from rice and peanut and identified as Penicillium charlesii and Aspergillus candidus on the basis of morpho-molecular characteristics A sensitive, rapid and robust analytical method was developed and validated to determine the aflatoxin contamination level in aforementioned peanut and rice matrices. The method involved methanolic extraction of aflatoxin, immune affinity column clean-up followed by derivatisation with Kobra cell and fluorescence detection. The analysis of contaminated samples revealed only two peanut samples and one rice sample possessed aflatoxin B1 and traces of aflatoxin B2. The method showed 0.05 µg kg-1 as the limit of quantification which was below the maximum levels set by various global regulations. The method performance was in line with the performance criteria established by numerous regulatory bodies such as EU and SANTE.